Non-CEO executive mobility: The impact of poor firm performance and TMT attention. Issue 4 (August 2015) - Buyl, Tine; Boone, Christophe; Wade, James B.
Abstract We present a comprehensive and integrative study of non-CEO executive mobility, proposing two complementary approaches: (1) mobility as a reactive process, driven by poor organizational performance (the dominant approach in prior literature) and (2) mobility as a proactive process, reflecting incumbent TMTs' patterns of (exploratory and exploitative) attention. Using a sample of 1168 observations proceeding from 197 US organizations (2000–2011), we empirically validate that non-CEO executives' exit and inflow is driven by poor organizational performance, and that CEO replacement mediates this effect (i.e., the so-called 'sweep-out effect'). Furthermore, the probability of non-CEO executive inflow is higher when the incumbent TMT has a high level of exploratory attention and lower when there is a high level of exploitative attention. These 'proactive' effects occur over and above the 'reactive' processes of poor organizational performance.